Mental health professionals' awareness of the parental functioning of persons with severe mental disorders: a retrospective chart study - Shahar Eliezer; Martin Efron; Shlomo Mendlovic; Gilad Gal; Ido Lurie (BMC, 2022)
Abstract Background: The proportion of persons with severe mental illness (SMI) who are parents has increased in recent decades. Children of parents with SMI are at increased risk for medical, behavioral, emotional, developmental, academic, and social problems. They also have an increased risk for injuries, accidents, and mortality, addictions, and various psychiatric disorders compared to children of parents with no such diagnoses. We aimed to examine the extent to which mental health professionals (MHPs) who treat adult patients with SMI in ambulatory settings are aware of these individuals' functioning in three parenting domains: parental functioning, familial support system and children's conditions. We also compared psychiatrists' awareness with that of psychologists and social workers. Methods: In this retrospective practice-oriented study, we reviewed 80 clinical files of individuals diagnosed with schizophrenia, affective disorder or personality disorder treated in a mental health outpatient clinic, using the Awareness of Family's Mental Health Checklist (AFMHC) developed for this study. Thus, awareness was determined on the basis of what was recorded in the patient file. Results: Almost half of the MHPs were unaware to their patients' parental functioning as only 44% of files contained records relating to this issue. Awareness to other domains was even lower: 24% of files contained information on patient's support system and 12% had information about their children's mental and/or physical health. No statistically significant differences between psychiatrists and other MHPs were found with regards to awareness to the various domains. Positive correlations were found among MHP's for awareness in the three domains. Conclusion: Lack of awareness among MHPs to their patients' parental functioning is not specific to a certain profession and may be attributed to patients (e.g., reluctance to disclose relevant information) or to MHPs (e.g., lack of training). Awareness of family and parental functioning by MHPs working with persons with SMI should be part of a standard procedure, integrated into policy and training.